Maisy makes lemonade - Cousins, Lucy (Cambridge, MA : Candlewick Press, 2002)
On a hot day, Maisy the mouse and Eddie the elephant make lemonade and enjoy it together.
Keywords: Mice -- Fiction; Elephants -- Fiction; Lemonade -- Fiction